2004
DOI: 10.1093/tropej/50.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Rare CFTR Mutation 1525-1G〉A in a Pakistani Patient

Abstract: Cystic fibrosis (CF) is rare in non-Caucasian populations, and in such populations little is known about the spectrum of mutations and polymorphisms in the cystic fibrosis transmembrane conductance (CFTR) gene. We report the detection of a very rare CFTR mutation 1525-1G>A in intron 9 in a 5-year-old Pakistani child with typical clinical features of CF. It remains to be seen whether mutation 1525-1G>A is characteristic of Pakistani ethnicity with CF or associated with severe phenotypic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Unlike other countries where F508del is the most common mutation, this study showed that c.1393-1G>A (legacy name: 1525-1G>A) is the most occurring CFTR mutation among a cohort of Palestinians affected by CF despite the fact that this mutation is infrequent in the neighboring countries, and considered rare worldwide [ 19 ]. This splicing mutation was first described in 1993 in a CF patient of Indo-Iranian origin [ 20 ], and a subsequent study reported three Pakistani patients, two were homozygous and the third patient was heterozygous [ 21 ]. Recently, unlike the initial report by Wahab et al from Pakistan [ 21 ], Nikolic and co-workers stated that no homozygotes for this mutation have been reported so far [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other countries where F508del is the most common mutation, this study showed that c.1393-1G>A (legacy name: 1525-1G>A) is the most occurring CFTR mutation among a cohort of Palestinians affected by CF despite the fact that this mutation is infrequent in the neighboring countries, and considered rare worldwide [ 19 ]. This splicing mutation was first described in 1993 in a CF patient of Indo-Iranian origin [ 20 ], and a subsequent study reported three Pakistani patients, two were homozygous and the third patient was heterozygous [ 21 ]. Recently, unlike the initial report by Wahab et al from Pakistan [ 21 ], Nikolic and co-workers stated that no homozygotes for this mutation have been reported so far [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This splicing mutation was first described in 1993 in a CF patient of Indo-Iranian origin [ 20 ], and a subsequent study reported three Pakistani patients, two were homozygous and the third patient was heterozygous [ 21 ]. Recently, unlike the initial report by Wahab et al from Pakistan [ 21 ], Nikolic and co-workers stated that no homozygotes for this mutation have been reported so far [ 19 ]. Interestingly, this mutation was detected in six families out of the twenty one involved in our study in both homozygous (28.6%), and heterozygous (4.8%) forms.…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian study which detected this case suggests that the prevalence and natural history of CF in South Asians is similar to that among individuals of European origin [41]. This mutation has been reported in Pakistani and Afghan patients who showed severe phenotypic features [38, 42, 43]. Nevertheless a Serbian patient homozygous for the same mutation showed a mild form of CF [44].…”
Section: Discussionmentioning
confidence: 52%
“…Abdul Wahab et al described the case of a Syrian CF child homozygous for the ΔF508 mutation with severe clinical manifestations [17]. The 1525-1G > A mutation associated with severe CF was found in a Pakistani child reported on by Abdul Wahab et al [18]. The N1303K homozygous mutation was detected in an Egyptian child with pseudo-Bartter’s syndrome and was reported on in two case reports discussing the various findings [19, 20].…”
Section: The History Of Cystic Fibrosis In Qatarmentioning
confidence: 99%